DEVELOPMENT OF COMMUNICATIVE-SPEECH COMPETENCE OF FUTURE PRIMARY SCHOOL STUDENTS - Jurayeva Mukhtasar Abdukahharovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article thoroughly analyzes the problems of the development of communicative-speech competence of future primary school students and based on the conclusions drawn, proposals were developed.